2009
DOI: 10.4000/books.ifpo.673
|View full text |Cite
|
Sign up to set email alerts
|

Les cadis d'Iraq et l'État Abbasside (132/750-334/945)

Abstract: En 132/750, les Abbassides s’emparèrent du pouvoir au terme d’un mouvement dénonçant l’injustice des Umayyades. La réforme de l’appareil judiciaire, contribuant à affermir leur légitimité, fut une des réalisations majeures de la nouvelle dynastie. La centralisation de la justice, l’uniformisation juridique et l’étroite association des cadis au souverain firent de la judicature un instrument politique essentiel aux yeux du califat. Les Abbassides ne pouvaient pourtant prévoir les conséquences de cette réfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…31 Unfortunately, historical sources provide little information on the functioning of police courts, perhaps in part because police officers, who were regarded as violent soldiers, were usually unpopular in the scholarly circles that produced our texts. 32 Because of this lack of consideration, adab literature offered a smaller place to police officers who conducted daily investigations than it did to the qadis. Should one recognize here the origins of the marginal nature of police investigation in contemporary literature?…”
Section: Resultsmentioning
confidence: 99%
“…31 Unfortunately, historical sources provide little information on the functioning of police courts, perhaps in part because police officers, who were regarded as violent soldiers, were usually unpopular in the scholarly circles that produced our texts. 32 Because of this lack of consideration, adab literature offered a smaller place to police officers who conducted daily investigations than it did to the qadis. Should one recognize here the origins of the marginal nature of police investigation in contemporary literature?…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, the sense of "fulfilment" 43 carried by the root q.ḍ.y. finds a particular meaning when talking about debts: qaḍā daynan means "he settled a debt, paid off a debt," 44 an expression attested in documents from the first/seventh century. Thus, the receipt that we are reediting here (1), which dates from the decade of the 20s/640s, if not from the year 20 itself, begins with hādhā mā qaḍā ("here is what he paid"), as does the unedited document P. Louvre Inv.…”
Section: Qaḍāʾ = Reimbursement?mentioning
confidence: 99%
“…their social extraction, the habilitation of professional witnesses), judicial corruption -the latter revealing a social sub-system with distinct values 2 -and the chief qadi's court as a singular space at odds with ordinary courts revealing the political workings of judgeship. 3 Recent scholarship has also demonstrated that factors like arbitrariness and irrationality are no longer valid to explain qadis' adjudicative performances. Concerned researchers can work now with a better awareness of the risks of "essentializing" qadiship, e.g.…”
Section: State Of the Artmentioning
confidence: 99%